Pengembangan Modul Pembelajaran Fisika Berbasis Saintifik pada Materi Momentum dan Impuls Kelas X SMA - Casmunah Casmunah; Indica Yona Okyranida; Nurhayati Nurhayati (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The purpose of this research is to develop scientifically based physics learning modules on high school X grade momentum and impulse materials and know the feasibility of modules based on expert validation by lecturers and teachers as well as student responses. This type of research is research and development with the ADDIE model. ADDIE development model in which there are several stages, including: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The results showed that: the results of each stage of the physics learning module development have been validated and revised based on the advice of experts and have been tested to students as respondents. Development using the ADDIE model obtained results including assessments by experts of 81.80% of student response tests with a percentage of 80.04%. From the results of the test, it can be concluded that the development of scientific-based physics learning modules in high school X grade momentum and impulse materials deserves to be used as teaching materials.